Inversão conjunta de dados gravimétricos magnéticos e resistivo - SOUZA, Cleomar Fernandes de (Universidade Federal do Pará, 2014)
Despite its advantages, the application of joint inversion to real data is not a current practice. One of the difficulties involving joint interpretation of geophysical data is the lack of systematic studies designed to assess its performance in a variety of simulated geological settings. This thesis is a contribution to this kind of study. This thesis compares the inversion of three sets of geophysical data: gravity, magnetic, and resistivity. The standard inversions of each set are compared with the 3 possible joint inversions of two sets of data, and also with the joint inversion involving the three sets. The comparison is performed using sinthetic data produced by a two-dimensional rectangular prism with finite thickness, and the least squares method is employed in the solution of the standard nonlinear problem of determining the prism parameters. The criteria adopted for the comparison were the parameter estimates themselves, the parameter standard deviations (for gravity and magnetic inversion of noise corrupted data), and also the reduction of ambiguity detected by the dependence of the parameter estimates on the initial guess. We found that, in general, the joint inversion using two sets of data produces better results than the inversion of each individual set. On the other hand, the results of the joint inversion employing all three sets are similar to the results of the joint inversions using two sets of data. In some cases, however, the joint inversion using all three sets is the only one virtually independent of the initial guess. Applications to real anomalies are presented.